2018
DOI: 10.1021/acsami.8b10589
|View full text |Cite
|
Sign up to set email alerts
|

All Polymer Solution Processed Electrochromic Devices: A Future without Indium Tin Oxide?

Abstract: The growing range of applications for optoelectronic and electrochromic devices (ECDs) encourages the search for materials combining high electrical conductivity with optical transparency. Next generation transparent conducting electrodes (TCEs) are required to be inexpensive, lightweight, scalable, and compatible with flexible substrates to trigger innovations towards supporting sustainable living and reducing energy consumption. Here we show that PEDOT:PSS can be solution processed using blade coating and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 62 publications
2
49
0
Order By: Relevance
“…After an initial electrochemical conditioning between 0.8 and back to -0.2V, the charge neutral peak of PProDOT appears with the typical vibronic features and vibrant magenta/purple color [31] seen in Adv. [43][44][45] While electrochromic polymers on these films switch more rapidly than on doped PE 2 , the films are significantly more colored than the PE 2 -based films due to tailing of the PEDOT bipolaron band. 2019, 9,1900395 Figures 3 a,b, respectively, when the potential is set at -0.2 V. When the potential is changed to 0.8 V the visible absorption of the PProDOT is bleached (ΔT = 48%) and the film becomes color-neutral, as shown in Figure 3b (also see Figure S6 in the Supporting Information).…”
Section: Evaluation Of Pe 2 As a Transparent Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…After an initial electrochemical conditioning between 0.8 and back to -0.2V, the charge neutral peak of PProDOT appears with the typical vibronic features and vibrant magenta/purple color [31] seen in Adv. [43][44][45] While electrochromic polymers on these films switch more rapidly than on doped PE 2 , the films are significantly more colored than the PE 2 -based films due to tailing of the PEDOT bipolaron band. 2019, 9,1900395 Figures 3 a,b, respectively, when the potential is set at -0.2 V. When the potential is changed to 0.8 V the visible absorption of the PProDOT is bleached (ΔT = 48%) and the film becomes color-neutral, as shown in Figure 3b (also see Figure S6 in the Supporting Information).…”
Section: Evaluation Of Pe 2 As a Transparent Electrode Materialsmentioning
confidence: 99%
“…PEDOT:PSS films have also found use as transparent electrodes for electrochromic polymers and other applications. [43][44][45] While electrochromic polymers on these films switch more rapidly than on doped PE 2 , the films are significantly more colored than the PE 2 -based films due to tailing of the PEDOT bipolaron band. [19,23,43,46,47] This difference between the color neutrality of oxidized PE 2 and PEDOT has been previously investigated [19] and can be quantitatively observed by comparing the colorimetry of doped PE 2 films, either with ( Figure 3b) or without ( Figure S4b, Supporting Information) an oxidized film of PProDOT, with the reported values for PEDOT:PSS.…”
Section: Evaluation Of Pe 2 As a Transparent Electrode Materialsmentioning
confidence: 99%
“…However, since silver is electrochemically active in the same potential range as the majority of cathodically coloring electrochromic polymers (ECPs), it makes sense to eliminate it as an electrode material and utilize solely PEDOT:PSS. In addition to being redox‐stable, PEDOT:PSS can be rendered highly conductive using a variety of acidic post treatments . As it can be easily formulated into printable, aqueous inks, PEDOT:PSS is a promising candidate for transparent electrodes applied to paper ECDs.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(3,4‐ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as a water‐soluble conductive polymer has received extensive attention in the field of organic electroluminescence, solar cell, and sensor . Kim et al demonstrated that PEDOT:PSS films with highly enhanced conductivity and stability by heating treatment could serve as a promising transparent electrode for low‐cost and flexible ITO‐free organic solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(3,4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as a water-soluble conductive polymer has received extensive attention in the field of organic electroluminescence, solar cell, and sensor. [31,32] Kim et al [33] demonstrated that PEDOT:PSS films with highly enhanced conductivity and stability by heating treatment could serve as a promising transparent electrode for low-cost and flexible ITO-free organic solar cells. Hsiao and coworkers [34] prepared Ni(OH) 2 /PEDOT: PSS composites ["P-Ni(OH) 2 "] that enhanced the electric/ionic transport properties of pristine Ni(OH) 2 , and significantly reduce the charge transport barrier.…”
mentioning
confidence: 99%